The Cultural Environment of Popular Music Discourses in Contemporary Ghana: A Media and Communication Approach - Eugene Agbasi Adjoteye (Budapest International Research and Critics University, 2021)
The field of popular music is important within the cultural matrix of contemporary Ghana. This paper posits the cultural environment of contemporary music discourses in Ghana as a relevant and significant terrain of media and communication worthy of research in Africa. The paper also sets off the relationship between popular music discourses and micro-identity formation in Ghana and subsequently sets off the nexus between the systemic world and the life world of contemporary Ghanaian quotidian sphere. The first part discusses the terrain of contemporary music discourses in Ghana, whilst the second part treats the emerging issues in terms of popular music discursive functionality and dysfunctionality within the interstices of the Ghanaian cultural environment.